Critical Pedagogy on Argumentative Text Material in Indonesian Language Book for Grade XI High School - Hardinanto, Eko; Ma’rifatulloh, Sayid; Indrawan, Fani; Faizi, Ahmad; Dwinata, Anggara; Raharja, Hawwin Fitra (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2025)
This study aims to determine the elements of critical pedagogy and the presentation of critical pedagogy in argumentative text materials in Indonesian language textbook for grade XI high school. This study is a qualitative descriptive study. The problem to be analyzed is the Indonesian language textbook for high school published by the Ministry of Education and Culture, using a critical pedagogy approach. The materials in the Indonesian language textbook for grade XI high school must apply critical perspective education or critical pedagogy, as a manifestation of the mandate of the Minister of Education and Culture. Argumentative text material is material that can be seen in its critical pedagogy elements. This study uses the Norman Fairclough critical discourse analysis research method, which is divided into three elements, namely text elements, discourse practice elements, and sociocultural practice elements. The results of this study indicate that the text analysis, vocabulary was found that characterizes critical pedagogy. In the analysis of discourse practice, the critical pedagogy that emerged was only an incomplete critical pedagogy. Then, for the analysis of sociocultural practice, the results of the PISA ranking and the pandemic that caused the economic recession, were the causes of critical pedagogy not emerging completely.